2011
DOI: 10.1586/erc.11.167
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity assessment: explaining the association between obesity, hypertension and stroke

Abstract: Obesity is associated with a greater prevalence of cardiovascular risk factors and a higher risk of cardiovascular events, and contributes to the rise in cardiovascular morbidity and mortality worldwide. Increased BMI is established as an independent risk factor for cardiovascular disease (CVD). Attention has recently been drawn to alternate measures of adiposity/obesity, such as waist circumference, waist-to-hip ratio and waist-to-height ratio, that provide information regarding body fat distribution. Althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 75 publications
0
24
0
2
Order By: Relevance
“…adipokines | maternal-fetal exchange | amino acids | glucose | insulin resistance O besity and the metabolic syndrome are major risk factors for a wide array of diseases, including type 2 diabetes mellitus, cardiovascular disease, and cancer (1,2). Compelling evidence shows that metabolic syndrome is caused, in part, by a suboptimal intrauterine environment (3).…”
mentioning
confidence: 99%
“…adipokines | maternal-fetal exchange | amino acids | glucose | insulin resistance O besity and the metabolic syndrome are major risk factors for a wide array of diseases, including type 2 diabetes mellitus, cardiovascular disease, and cancer (1,2). Compelling evidence shows that metabolic syndrome is caused, in part, by a suboptimal intrauterine environment (3).…”
mentioning
confidence: 99%
“…For example, the performance of BMI might not be optimal in special circumstances such as childhood, elderly patients, or different ethnicities [3]. Predicting cardiovascular risk is one of the major reasons for calculating BMI, but BMI might be inferior to measures of abdominal obesity in this regard [10]. Anthropometric method is another tool by which we can measure adiposity and predict CKD.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the dangers of abdominal obesity, only few studies have reported on its prevalence among stroke survivors [17][18][19] and this dearth may have implications for effective primary and secondary stroke prevention. For instance, information on abdominal obesity among stroke survivors may provide insight into its contribution to stroke incidence [17][18][19] and may also indicate the possibility of a recurrent stroke in the future.…”
Section: Abdominal Obesity In Strokementioning
confidence: 99%
“…For instance, information on abdominal obesity among stroke survivors may provide insight into its contribution to stroke incidence [17][18][19] and may also indicate the possibility of a recurrent stroke in the future. It is, however, heartening that abdominal obesity can be successfully mitigated through educational and enlightenment programs to create awareness, and deliberate research and clinical focus on its prevalence, risk factors, prevention, and management.…”
Section: Abdominal Obesity In Strokementioning
confidence: 99%